2008
DOI: 10.1103/physrevlett.101.018104
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Properties and Population Asymptotics in the Population Balance Equation

Abstract: Proliferating cell populations at steady-state growth often exhibit broad protein distributions with exponential tails. The sources of this variation and its universality are of much theoretical interest. Here we address the problem by asymptotic analysis of the population balance equation. We show that the steady-state distribution tail is determined by a combination of protein production and cell division and is insensitive to other model details. Under general conditions this tail is exponential with a depe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 20 publications
(30 reference statements)
3
38
0
Order By: Relevance
“…a result that is consistent with the analysis of symmetric cell division as performed in [28]. In the same work, it was shown that this asymptotic behavior occurs also under generic assumptions about asymmetric division.…”
Section: Binary Divisionsupporting
confidence: 77%
“…a result that is consistent with the analysis of symmetric cell division as performed in [28]. In the same work, it was shown that this asymptotic behavior occurs also under generic assumptions about asymmetric division.…”
Section: Binary Divisionsupporting
confidence: 77%
“…Earlier work focused on protein accumulation and division [18][19][20][21][22], or protein accumulation and continuous dissipation [23,24]. The recent data on protein content over multiple generations [8] shows that, due to the exponential nature of protein accumulation, division or dissipation alone cannot stabilize copy numbers, and reveal a correlation between variables across generations.…”
Section: Discussionmentioning
confidence: 99%
“…In Ref. [16], the situation was just opposite: Protein partitioning was stochastic and protein production was deterministic. After combining the stochastic protein production (of Ref.…”
Section: Discussionmentioning
confidence: 99%
“…[16]. If x cannot be treated as proportional to the cell mass or volume, it is unclear how the division rate should depend on the copy number of a given protein, and various functional forms of h d (x) were used in the literature [14][15][16]. For that reason, and in order to obtain an analytically tractable model, we focus here on the simplest case of the constant cell division rate, 2h d (x) ≡ ∆ = const, which implies ∞ 0 h d (ξ)p(ξ)dξ = ∆/2.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation